2022
DOI: 10.1371/journal.pone.0276994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a three-week executive control training on adaptation to task difficulty and emotional interference

Abstract: Intact executive functions are characterized by flexible adaptation to task requirements, while these effects are reduced in internalizing disorders. Furthermore, as executive functions play an important role in emotion regulation, deficits in executive functions may contribute to symptom generation in psychological disorders through increased emotional interference. Thus, the present study investigated transfer effects of a three-week executive control training on adaptation to task difficulty and emotional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
1
0
0
Order By: Relevance
“…Furthermore, the signal-N2 latency was also shorter after the combined tVNS with ICT intervention in fronto-central and central regions, and this effect was not seen in the sham tVNS or sham ICT groups. This is consistent with the hypothesis that tVNS exerts a positive synergistic effect on IC enhancement, which, in turn, produces an accelerating effect of automatically generated response tendencies ( Grützmann et al, 2022 ). This has been corroborated by findings from Pihlaja et al (2020) who suggested that a change in the frontal N2 component is a neural marker of cognitive control.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the signal-N2 latency was also shorter after the combined tVNS with ICT intervention in fronto-central and central regions, and this effect was not seen in the sham tVNS or sham ICT groups. This is consistent with the hypothesis that tVNS exerts a positive synergistic effect on IC enhancement, which, in turn, produces an accelerating effect of automatically generated response tendencies ( Grützmann et al, 2022 ). This has been corroborated by findings from Pihlaja et al (2020) who suggested that a change in the frontal N2 component is a neural marker of cognitive control.…”
Section: Discussionsupporting
confidence: 91%